Answer:
The expression that is equivalent to -6x+9y would be -3(2x-3y)
Answer:
x=-2
Step-by-step explanation:
Hey there!
In order to solve this equation, you need to combine like terms
The equation after combining the x terms and the contants will look like this
10x+3=12x+7
Now you have to take 10x away from both sides
3=2x+7
Now bring all the constants to the left side
3-7=2x
Simplify
-4=2x
divide 2 on both sides to get x by itself
x=-2
So, the answer is x=-2
16 because you divide i hour by 15 and multiply that by 4:)
Answer:
2/(3x-2)²
Step-by-step explanation:
4x²-6x³-2x²+6x³/4x²-6x³-6x³+9x^4=
2x²/4x²-12x³+9x^4=
2x²/x²(4-12x+9x²)=
2/9x²-12x+4
2/(3x-2)²
The radical function is 3√x + 1.
Since the cubic root of zero is zero, 0 would be x.
Add zero and one, which gives you 1. 1 is y.
You get (0,1)
Since this is a positive radical, it would be going to the top right.
So, the domain is x ≥ 0
the range is y ≥ 1